Personal narrative of a pilgrimage to El-Medinah and Meccah - Burton, Richard Francis, Sir, 1821-1890 (Cambridge library collection., 2012)
A vivid account of the hajj in 1853, by a British explorer who travelled to Mecca disguised as a pilgrim.